Appearance Stylization of Manhattan World Buildings. (10th October 2013) - Li, C.; Willis, P. J.; Brown, M.
<x xml:space="preserve">Abstract</x> We propose a method that generates stylized building models from examples. Our method only requires minimal user input to capture the appearance of a Manhattan world building, and can automatically retarget the captured "look and feel" to new models. The key contribution is a novel representation, namely the "style sheet", that is captured independently from a building's structure. It summarizes characteristic shape and texture patterns on the building. In the retargeting stage, a style sheet is used to decorate new buildings of potentially different structures. Consistent face groups are proposed to capture complex texture patterns from the example model and to preserve the patterns in the retarget models. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>